Incidence, Clinical Characteristics and Outcomes Associated with Acute Kidney Injury in Patients Hospitalized with COVID-19 - Shrestha, Sanjay; Maharjan, Kijan; Bajracharya, Milan; Sharma Chalise, Bimal; Balla, Pujan; Adhikari, Shambhu; Shrestha, Soni; Baral, Bishwodip; Neupane, Jenish; Poudel, Manu; Bastola, Anup (Journal of Nepal Health Research Council, 2024)
Background: Acute kidney Injury associated with Coronavirus disease COVID-19 appeared to negatively influence clinical outcomes and is found to be associated with significant risk of death. This retrospective study aimed to describe the incidence of Acute Kidney Injury, its associations with clinical characteristics and outcomes among COVID-19 patients in Sukraraj Tropical and Infectious Disease Hospital, a tertiary infectious disease hospital in Nepal. Methods: A cross-sectional study was done where. Medical and lab records of reverse transcriptase Polymerase chain reaction positive COVID-19 inpatients, admitted between April 2021 to July 2021 were reviewed. It represented the second wave of wave of coronavirus pandemic caused by the delta strain. Patients aged less than 18 years, pregnant females and patients with known chronic kidney disease were excluded Results: Of 393 admissions, 83 (21.1%) patients developed Acute Kidney Injury. Characteristics found to have significant association with development of AKI was age (p <0.001), multiple co morbidities (2 or more) (p <0.001), use of mechanical ventilation (p <0.001), lymphopenia (p<0.001), Neutrophil to Lymphocyte Ratio (p =0.001) and d-dimer levels (p <0.001). Mortality was found to be significantly higher in COVID-19 patients with AKI compared to COVID-19 patients without AKI ((36.14% vs 15.8%, p value <0.01)). The median duration of hospital stay for patients with AKI was higher than for patients without AKI (10 days vs 6 days,p <0.01). Conclusions: AKI develops in a sizeable percentage of patients with COVID-19 and is significantly associated with increasing age, multiple comorbidities, increased biomarkers, use of mechanical ventilation and is associated with poor outcome in terms of mortality and morbidity. Keywords: AKI; COVID-19; Nepal; outcomes.